Charity case how the nonprofit community can stand up for itself and really change the world - Pallotta, Dan. (San Francisco Jossey-Bass, 2012)
Virtually everything our society has been taught about charity is backwards. We deny the social sector the ability to grow because of our short-sighted demand that it send every short-term dollar into direct services. Yet if the sector cannot grow, it can never match the scale of our great social problems. In the face of this dilemma, the sector has remained silent, defenseless, and disorganized. In Charity Case, Pallotta proposes a visionary solution: a Charity Defense Council to re-educate the public and give charities the freedom they need to solve our most pressing social issues. Proposes concrete steps for how a national Charity Defense Council will transform the public understanding of the humanitarian sector, including: building an anti-defamation league and legal defense for the sector, creating a massive national ongoing ad campaign to upgrade public literacy about giving, and ultimately enacting a National Civil Rights Act for Charity and Social Enterprise From Dan Pallotta, renowned builder of social movements and inventor of the multi-day charity event industry (including the AIDS Rides and Breast Cancer 3-Days) that has cumulatively raised over
Includes bibliographical references (p. 199-218) and index.
Keywords: Charity organization. Nonprofit organizations